Engineered Maturation Approaches of Human Pluripotent Stem Cell-Derived Ventricular Cardiomyocytes - Ge, Feixiang (Cells, 2019)
Heart diseases such as myocardial infarction and myocardial ischemia are paroxysmal and fatal in clinical practice. Cardiomyocytes (CMs) differentiated from human pluripotent stem cells provide a promising approach to myocardium regeneration therapy. Identifying the maturity level of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) is currently the main challenge for pathophysiology and therapeutics. In this review, we describe current maturity indicators for cardiac microtissue and microdevice cultivation technologies that accelerate cardiac maturation. It may provide insights into regenerative medicine, drug cardiotoxicity testing, and preclinical safety testing.